Advancing performance measurement. Issue 1 (12th January 2015) - Manes Rossi, Francesca; Aversano, Natalia
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to analyse the implementation of performance measurement tools by medium-to-large size Italian Local Governments (ILGs) with the aim of establishing their position in comparison with the content of the International Public Sector Accounting Standards Board's (IPSASB's) Consultation Paper (CP) on Reporting Service Performance Information and the points of views of other countries. Design/methodology/approach – A survey of all ILGs with more than 50, 000 inhabitants has been carried out with the objective of evaluating which kind of performance management tools are implemented; moreover, these results are compared with the content of the IPSASB's CP to evaluate the role of this guide as well as the main differences between the IPSASB's approach and the current situation in Italy. Findings – Data collected highlight that several performance measurement tools required by law are generally prepared in ILGs even if a limited use of them for decision-making or accountability purposes occurs. Moreover, in accordance with the opinions of the countries that submitted letters of comment to IPSASB's CP, Italian results reveal that information on the scope of the service performance information, on the entity's objectives and their achievement, including a narrative discussion of this achievement, are perceived as relevant. Originality/value – The research investigates the future development of the CP by analyzing the points of view of the countries that submitted letters of comments to IPSASB. It also examines whether the current Italian situation is in line with the IPSASB's position.